Rancang Bangun Aplikasi Kamus Percakapan Bahasa Arab Berbasis Mobile Menggunakan Teknologi J2ME - Saputra, Renanda Cahya; Sutanto, Teguh; Sagirani, Tri (Jurnal JSIKA, 2012)
Most people who travel abroad are not really mastery the language of the country they visited, so they are having difficulties  to communicate with local people. This condition can be met when Indonesian people held hajj or umrah every single year in Saudi Arabia. Based on the survey’s result that author has been done to 30 respondents, there is a fact that 93,33% respondents are having difficulties to communicate using Arabic language when they do hajj or umrah. One of the solutions to solve this problem is making an arabic conversation dictionary application based on mobile technology using J2ME. This dictionary application is able to search words and show conversations in various situasion then, this application, can add some new words that can be done manually by its user and those words can be edited or deleted. Based on test-run that have been done to the respondents, the result shows that the Arabic conversation dictionary application based on mobile technology using J2ME could simplify and help the hajj and umrah worshippers who are struggled to communicate in Arabic.” Keywords : Mobile application, Arabic dictionary, J2ME